Participatory Approach in Developing an Islamic Community Based on Local Wisdom - Dewi, Rosa; Aziz, Safiullah; Zaman, Khalil; Firdaus, Anang (Journal International Dakwah and Communication, 2024)
Community development in Islamic societies requires an approach that integrates religious values and local wisdom to ensure sustainability and social cohesion. Conventional top-down development models often fail to capture the unique cultural and spiritual dynamics that shape community participation. A participatory approach, which actively involves local stakeholders in decision-making processes, is essential for fostering self-reliance, cultural preservation, and community-driven development. Understanding how participatory strategies contribute to building Islamic communities grounded in local traditions is crucial for developing inclusive and effective community empowerment programs. This study aims to examine the role of participatory approaches in developing Islamic communities while incorporating local wisdom as a foundational element of social engagement. A qualitative research design is employed, utilizing ethnographic fieldwork, in-depth interviews, and participatory observation in selected Islamic communities. Findings reveal that community-led initiatives, collaboration with religious leaders, and integration of traditional customs strengthen collective identity and social trust. Participatory approaches facilitate knowledge-sharing, conflict resolution, and resource management, leading to a more resilient and self-sustaining Islamic community structure. The study concludes that Islamic community development must balance religious teachings with localized cultural practices to foster social harmony and sustainability. Recommendations for integrating participatory frameworks into Islamic community development policies are discussed.